Design and development of an E-learning platform software application - Goh Keng An (2017)
With the rapid advancement of portable devices, computers and multimedia technologies, together with incredible internet speed and bandwidth, have fused multimedia with learning. NTU has been using Blackboard Learn, a broadly used eLearning software, together with LAMS to conduct eLearning. However, Blackboard is just presentation of content and LAMS can only provide one feature at a time in each activity of a lesson. Gagne, who was an American educational psychologist, engineered a learning framework (“Conditions of Learning”) for intellectual skills consisting of nine consecutive steps. This project’s objective was to develop a deployment platform for eLearning software application following the Gagne’s framework together with two mini games to provide necessary conditions of learning and better sequencing of the complexity of course content while the mini games are to enhance the learning experience. This project was developed by using the traditional waterfall model of Software Development Life Cycle so as to strictly follow the requirements and milestones. This project was developed using Bootstrap for responsive views and ASP.NET framework using three-tier architecture. This project was beta-tested with positive results and a few drawback comments. The student users’ survey showed remarkable positive results on this project. On the other hand, the professor user gave positive comments while providing some minor drawbacks on the usability, which can be solved by user manual or further minor improvements. The author applied the skills and knowledge learned in school for this project and learned some mistakes on his way. However, he learned a lot of skills more than he ever did during this project development. The author also provides some recommendations for future work.